Targeted and immunotherapeutic approaches in brain metastases - Ahluwalia, Manmeet S.; Winkler, Frank (Educational book, 2015)
Brain metastases are a common and devastating complication of cancer. The approach to the management of brain metastases is often multidisciplinary and includes surgery, whole-brain radiation therapy (WBRT), stereotactic radiosurgery (SRS), and systemic therapeutic agents. Until recently, systemic therapy has had a limited role in the management of brain metastases because of a lack of activity, challenges of blood-brain barrier penetration, the heterogeneous patient population, and a heavily pretreated patient population. Advances in the understanding of the biology of brain metastases and molecularly defined disease subsets have facilitated an emerging role of novel therapeutic agents, including targeted therapies and immunotherapy, in the management of brain metastases.
Gesehen am 14.10.2020